Семантика металлических украшений периода Средневековья на материале могильников Сургутского Приобья - Сизова, Анна Олеговна (Издательский центр СурГУ, 2020)
Статья посвящена семантике металлических украшений, их значению в костюме аборигенного населения Сургутского Приобья.

The article is devoted to the semantics of metal jewelry and their significance in the costume of the aboriginal population of the Surgut Priobye.
SEMANTICS OF METAL JEWELRY IN THE MIDDLE AGES ON MATERIAL OF BURIAL GROUNDS OF SURGUT PRIOBYE